1996
DOI: 10.1002/(sici)1098-2795(199611)45:3<378::aid-mrd16>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate/CO2, an effector of capacitation, induces a rapid and reversible change in the lipid architecture of boar sperm plasma membranes

Abstract: Bicarbonate/CO2 is believed to be the key in vitro effector of sperm capacitation, a process which induces major changes in the sperm plasma membrane in preparation for fertilization. In a flow cytometric study, we examined the effect of bicarbonate on boar spermatozoa using merocyanine, an impermeant lipophilic probe which binds to plasma membranes with increasing affinity as their lipid components become more disordered. We found that bicarbonate causes a rapid increase in the ability of live boar spermatozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(53 citation statements)
references
References 0 publications
4
49
0
Order By: Relevance
“…Recent advances have revealed that in human spermatozoa, capacitation may be initiated by engagement of surface receptors (Nixon et al, 2006) and the subsequent induction of complex signaling pathways that ultimately converge to promote an impressive upregulation of tyrosine phosphorylation across myriad target proteins (Leclerc et al, 1996(Leclerc et al, , 1998Lefievre et al, 2002;Mitchell et al, 2008;Visconti et al, 1995aVisconti et al, , 1995b. While the precise mechanisms remain to be unequivocally established, these biochemical changes appear causally linked to the surface remodeling events that allow spermatozoa to adhere to the ZP (Cross, 2003;Gadella et al, 2008;Harrison et al, 1996;Harrison and Gadella, 2005;Myles and Primakoff, 1984;Yanagimachi, 1994).…”
Section: Introductionsupporting
confidence: 90%
“…Recent advances have revealed that in human spermatozoa, capacitation may be initiated by engagement of surface receptors (Nixon et al, 2006) and the subsequent induction of complex signaling pathways that ultimately converge to promote an impressive upregulation of tyrosine phosphorylation across myriad target proteins (Leclerc et al, 1996(Leclerc et al, , 1998Lefievre et al, 2002;Mitchell et al, 2008;Visconti et al, 1995aVisconti et al, , 1995b. While the precise mechanisms remain to be unequivocally established, these biochemical changes appear causally linked to the surface remodeling events that allow spermatozoa to adhere to the ZP (Cross, 2003;Gadella et al, 2008;Harrison et al, 1996;Harrison and Gadella, 2005;Myles and Primakoff, 1984;Yanagimachi, 1994).…”
Section: Introductionsupporting
confidence: 90%
“…Bicarbonate plays a major role in the activation of sperm cells (43). High levels of bicarbonate induce activation of adenylate cyclase, one of the key events in sperm capacitation that occurs in the lumen of the oviduct and is virtually absent in epididymal and seminal plasma (44). Under normal conditions, most of the freshly ejaculated spermatozoa are acrosome unreacted.…”
Section: Discussionmentioning
confidence: 99%
“…Capacitation allows spermatozoa to undergo the zona pellucida-induced acrosome reaction (AR) and fertilize oocytes. Although the molecular mechanisms of capacitation are not completely elucidated, many studies have demonstrated an involvement of numerous structural and biochemical modifications in spermatozoa, such as changes in membrane composition and fluidity [4][5][6], increased intracellular calcium [7][8][9], cytoplasmic alkalinization [10,11], activation of ion channels [12,13], and generation of reactive oxygen species [14,, 15]. Capacitation is associated with protein tyrosine phosphorylation [8,[16][17][18], which is modulated via a cAMPdependent pathway in many species, including the mouse, human, and bull [8, 19,, 20].…”
Section: Introductionmentioning
confidence: 99%